Role of riboflavin deficiency in malaria pathophysiology. - Shweta Sharma; Arathy Ramachandran; Amit Sharma (PLoS Pathogens, 2024)
The emergence of resistance against antimalarials and insecticides poses a significant threat to malaria elimination strategies. It is crucial to explore potential risk factors for malaria to identify new targets and alternative therapies. Malnutrition is a well-established risk factor for malaria. Deficiencies of micronutrients such as vitamin A, zinc, iron, folic acid, and phenotypic measures of malnutrition, such as stunting and wasting, have been studied extensively in the context of malaria. Vitamin B2, also known as riboflavin, is a micronutrient involved in maintaining cellular homeostasis. Riboflavin deficiency has been shown to have an inverse correlation with malarial parasitaemia. This article reviews the role of riboflavin in maintaining redox homeostasis and probes how riboflavin deficiency could alter malaria pathogenesis by disrupting the balance between oxidants and antioxidants. Though riboflavin analogues have been explored as antimalarials, new in vivo and patient-based research is required to target riboflavin-associated pathways for antimalarial therapy.